High mobility group box‐1 induces pro‐inflammatory signaling in human nucleus pulposus cells via toll‐like receptor 4‐dependent pathway. Issue 1 (29th October 2018) - Shah, Bhranti S.; Burt, Kevin G.; Jacobsen, Timothy; Fernandes, Tiago D.; Alipui, Didier Olivier; Weber, Kathryn T.; Levine, Mitchell; Chavan, Sangeeta S.; Yang, Huan; Tracey, Kevin J.; Chahine, Nadeen O.
ABSTRACT: Intervertebral disc (IVD) degeneration (DD) is associated with low back pain, the leading cause of disability worldwide. Damage‐associated molecular patterns (DAMPs) that contribute to inflammation and trigger DD have not been well characterized. Extracellular high mobility group box‐1 (HMGB1) protein has been implicated as a potent DAMP and pro‐inflammatory stimulus in the immune system. In this study, we show that HMGB1 and IL‐6 levels increase in patients with advanced DD in comparison to early DD. This study further tested the hypothesis that HMGB1 promotes inflammatory signaling driving DD in human nucleus pulposus (NP) cells and tissue. Immunofluorescence and western blot analysis confirmed the expression of HMGB1 and its extracellular release by NP cells under cell stress. Gene expression and protein quantification indicate that HMGB1 stimulates the expression IL‐6 and MMP‐1 in a dose‐dependent manner. The contributions of toll‐like receptor (TLR) −2, −4 and receptor for advanced glycation end products (RAGE) as receptors mediating HMGB1 signaling was examined using small molecule inhibitors. Inhibition of TLR‐4 signaling, with TAK‐242, completely abrogated HMGB1 induced IL‐6 and MMP‐1 expression, whereas inhibition of TLR‐2, with O‐vanillin, or RAGE, with FPS‐ZM1, had mild inhibitory effects. HMGB1 stimulation activated NF‐ĸB signaling while TAK‐242 co‐treatment abrogated it. Lastly, effects of HMGB1 on matrix deposition was evaluated in a 3D culture system of human NP cells. These results implicate HMGB1 as a potent DAMP that promotes inflammation in NP cells and degradation of NP tissues. TLR4‐HMGB1 axis is a potential major pathway to alleviate disc inflammation and mitigate DD. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res